2016
DOI: 10.1177/0194599816656169
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Assessment of Nasopharyngolaryngoscope Recording Adaptor Use in Residency Training

Abstract: Flexible fiberoptic nasopharyngolaryngoscope (FN) examinations are important to the practice of otolaryngology (ENT). We sought to assess whether a portable recording adaptor for the FN can enhance resident learning and improve patient management. The adaptor was used prospectively on consultations by first- and second-year ENT residents, and changes in diagnosis and management were recorded in the patient care workflow. In 43 patients, we found a 23% change in diagnosis, 44% change in management, and 19% chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 5 publications
0
13
0
Order By: Relevance
“…Similar to our study, comparisons were made between resident versus attending interpretations. The authors found a change between resident and attending diagnoses in 23% of patients, with a change in management occurring 44% of the time …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar to our study, comparisons were made between resident versus attending interpretations. The authors found a change between resident and attending diagnoses in 23% of patients, with a change in management occurring 44% of the time …”
Section: Discussionmentioning
confidence: 99%
“…In addition, during the course of this study, junior residents routinely reviewed recorded FL exams demonstrating commonly seen pathologies as a group, providing a unique educational experience. In the study by Liu et al, the vast majority of attendings and residents felt that the portable recording technology enhanced resident education …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A limited number of studies have investigated the value of recording endoscopic exams with smartphone adaptors in terms of diagnostic accuracy and resident education . However, only one previous study has looked at optical parameters .…”
Section: Discussionmentioning
confidence: 99%
“…A limited number of studies have investigated the value of recording endoscopic exams with smartphone adaptors in terms of diagnostic accuracy and resident education. [2][3][4][5] However, only one previous study has looked at optical parameters. 3 Liu et al found no significant difference in video quality ratings between endoscopy video tower recordings and smartphone adapter recordings.…”
Section: Discussionmentioning
confidence: 99%